Pelatihan Jurnalistik Dan Public Relations Bagi Siswa Syafana Islamic High School, Tangerang Selatan Oleh Program Studi Ilmu Komunikasi, Swiss German University - Deborah N. Simorangkir; Ezmieralda Melissa; Muninggar Sri Saraswati; A'an Suryana; Loina L.K. Perangin-Angin (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
With the proliferation of social media and the rampant spread of hoaxes in the community, it is important that efforts are made to provide the next generation with media literacy and communication provisioning. Therefore, on April 23, 2019, the Communication and Public Relations Study Program, Swiss German University, held a workshop entitled